2017
DOI: 10.1097/igc.0000000000001061
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Endometrial Cancer Patient–Derived Organoid Culture for Drug Sensitivity Testing Is Feasible

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 17 publications
(22 reference statements)
3
51
0
Order By: Relevance
“…In addition to benign endometrial organoid models, organoids have also been derived from endometrial cancer tissues, and used for drug testing. [65][66][67][68] These endometrial cancer organoids recapitulated genetic and phenotypic characteristics of endometrial tumors, and could be an efficient way of testing therapies. [66][67][68] Organoids have also been derived from the endometrium of patients with other diseases, including endometrial hyperplasia, Lynch syndrome, and endometriosis.…”
Section: Human Endometrial Organoids: Recapitulating Native Tissues Wmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to benign endometrial organoid models, organoids have also been derived from endometrial cancer tissues, and used for drug testing. [65][66][67][68] These endometrial cancer organoids recapitulated genetic and phenotypic characteristics of endometrial tumors, and could be an efficient way of testing therapies. [66][67][68] Organoids have also been derived from the endometrium of patients with other diseases, including endometrial hyperplasia, Lynch syndrome, and endometriosis.…”
Section: Human Endometrial Organoids: Recapitulating Native Tissues Wmentioning
confidence: 99%
“…[65][66][67][68] These endometrial cancer organoids recapitulated genetic and phenotypic characteristics of endometrial tumors, and could be an efficient way of testing therapies. [66][67][68] Organoids have also been derived from the endometrium of patients with other diseases, including endometrial hyperplasia, Lynch syndrome, and endometriosis. 65 Endometrial organoids have provided an alternate physiologic model of the endometrium that can be adapted to biobanking, drug screenings, and investigation of endometrial physiology and pathology.…”
Section: Human Endometrial Organoids: Recapitulating Native Tissues Wmentioning
confidence: 99%
“…Girda et al generated 15 organoids from 14 endometrial and 1 metastatic tumors. The organoids had similar morphological features to their parental tumors.…”
Section: Pdtos As Potential Tumor Models For Drug Screening and Drug mentioning
confidence: 99%
“…Therefore, since cost-effective techniques are required, in vitro systems, including patient-derived tumor organoid (PDO) or spheroid models that accurately recapitulate tissue architecture and function, have been developed recently. The establishment of human tumor organoids has been recently reported for colon ( 12 14 ), pancreatic ( 15 ), prostate ( 16 ), endometrial ( 17 ), and liver ( 18 ) tumors, among others. In particular, Pauli et al ( 19 ) reported 56 PDOs that were established from bladder, breast, brain, colon, lung, kidney, ovarian, pancreatic, prostate, stomach and uterine cancers, among others, in addition to the development of high-throughput screening (HTS) using these systems.…”
Section: Introductionmentioning
confidence: 99%